Altered imino diacid synthesis and transcription in crown gall tumors with transposon Tn5 insertions in the 3' end of the octopine synthase gene. - Chang, C C (1989)
Octopine synthase encoded by the T-DNA (transferred DNA) locus ocs synthesizes N2-(D-1-carboxyethyl)-L-amino acids in octopine-type crown gall tumors. So far, derivatives of only basic amino acids have been isolated. We have detected a glutamine derivative and called it heliopine. Tumors induced by several Ti plasmids with transposon Tn5 insertions in the 3' end of ocs still synthesized small quantities of N2-(1-carboxyethyl)-arginine and N2-(1-carboxyethyl)-glutamine. In addition, N2-(1,3-dicarboxypropyl)-asparagine, which is absent in wild-type octopine tumors, was detected in these tumors. These three imino diacids (octopine, heliopine, and asparaginopine, respectively, or their isomers) were undetectable in tumors induced by Ti plasmids harboring deletions of the ocs gene. Poly(A)+ RNAs which hybridize to the ocs sequence can also be detected in the ocs::Tn5 tumors; these RNAs, however, were heterogeneous in size and shorter in length than the normal ocs mRNA. These results indicate that mutant ocs products synthesize imino diacids in these ocs::Tn5 tumors.